1991
DOI: 10.1016/s0022-5347(17)37974-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Septicemia Following Endourological Manipulation for Stones in the Upper Urinary Tract

Abstract: We investigated 117 patients undergoing percutaneous nephrolithotomy, percutaneous nephrostomy, ureterorenoscopy, the push-back or push-bang procedure for ureteral stones, Double-J* ureteral stenting plus extracorporeal shock wave lithotripsy (ESWL), ESWL alone or cystoscopy. Blood samples obtained before, during and 1 hour after the procedure were cultured and assayed for endotoxin and tumor necrosis factor. Also, culture was done of the urine preoperatively and postoperatively, and the stones when they could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(82 citation statements)
references
References 14 publications
5
67
2
1
Order By: Relevance
“…In addition, a much higher rate of postoperative pyrexia (temperature >37.5°C) was observed in patients following PCNL surgery (74% of cases). Moreover, although the study by Rao et al 7 confirmed a statistically significant association between pre-operative bacteriuria and the development of postoperative bacteraemia (bacteraemia in 37% of patients with a positive MSSU compared to 8% in those with a negative urine culture pre-operatively), this was not observed in our analysis. The postoperative sepsis (temperature >38.5°C) rates were similar in those patients without pre-operative confirmed UTI.…”
Section: Complicationscontrasting
confidence: 82%
“…In addition, a much higher rate of postoperative pyrexia (temperature >37.5°C) was observed in patients following PCNL surgery (74% of cases). Moreover, although the study by Rao et al 7 confirmed a statistically significant association between pre-operative bacteriuria and the development of postoperative bacteraemia (bacteraemia in 37% of patients with a positive MSSU compared to 8% in those with a negative urine culture pre-operatively), this was not observed in our analysis. The postoperative sepsis (temperature >38.5°C) rates were similar in those patients without pre-operative confirmed UTI.…”
Section: Complicationscontrasting
confidence: 82%
“…An incidence of sepsis associated with obstructed uropathy and urinary stones treated surgically has also been reported in 1.28 % of cases (O'Keeffe et al, 1993). Rao et al (1991) found an incidence of septic shock after endoscopic manipulation for urinary stone in about 1% of treated patients. Sepsis is an advanced stage of uncontrolled systemic inflammatory response syndrome that may turn toward irreversible multiple organ failure and death.…”
Section: Sepsis and Urosepsismentioning
confidence: 98%
“…Septic shock following urinary stone manipulation was reported with an incidence of 1 % and mortality up to 80 % (Rao et al, 1991). In an effort to predict septicemia following endourological manipulation for stones in the upper urinary tract, 117 patients were studied and classified according to the procedure performed (Rao et al, 1991): Percutaneous nephrolithotomy, push-back/push-bang procedure, double-J and extracorporeal shock wave lithotripsy (SWL), ureteroscopy, SWL alone and only cystoscopy. Blood samples for bacterial culture, endotoxin and tumor necrosis factor assay were collected before, at onset, at the end and one hour after completing the procedure.…”
Section: Infected Urinary Stones and Urosepsismentioning
confidence: 99%
See 2 more Smart Citations